A study on infant and young child feeding practices among mothers attending the immunisation clinic of a tertiary care hospital, Kolkata, West Bengal - Chakraborty, Nabanita; Joardar, Gautam Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Age appropriate feeding practices is an essential determinant of physical growth as well as mental health of under-five children. WHO and UNICEF have formulated the infant and young child feeding practices guidelines to enhance appropriate feeding practices in infants and young children. Methods: A descriptive, observational, cross-sectional study was conducted in the immunization clinic of KPC medical college and hospital from October to December 2018 among children in 0-23 months age group. The mothers were interviewed regarding their sociodemographic details as well as the IYCF practices as per WHO. Results: It was found that appropriate practices in terms of prelacteal feeding, colostrum feeding; early initiation of breast feeding and exclusive breast feeding was present in 78.4%, 80%, 77.5% and 50% children respectively. Timely initiation of complementary feeding was found in 81%, breast feeding was continued upto 1 year in 68.8% and consumption of iron rich or iron fortified food was found in 54.5% children. Appropriate practices in terms of minimum meal frequency, minimum dietary diversity and minimum appropriate diet were found in 49.7%, 27% and 32.3% children respectively. Sex wise distributions have found significant association with minimum dietary diversity and minimum acceptable diet. Age wise distribution revealed significant association with minimum dietary frequency, minimum dietary diversity and minimum acceptable diet (p<0.005). Conclusions: Thus infant and young child feeding practices were not satisfactory. Mothers should be made aware about the appropriate feeding practices and health education should be given regarding correct child feeding practices.